Our experience of clinico-pathological study of thyroid swelling - Kirdak, Vilas R.; Chintale, Sambhaji G.; Jatale, Sonali P.; Shaikh, Kaleem A. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: Diseases of thyroid gland are extremely common. Majority of palpable thyroid swellings are asymptomatic occurs in 5% of the population. The main objective of present study is to know the accuracy of FNAC in preoperative diagnosis of clinically palpable thyroid swelling and evaluate the efficiency of FNAC, USG, and TFT in differentiating between benign and malignant thyroid swelling and their confirmation by histopathological reports after operation. Methods: This prospective study is carried out in 120 cases of thyroid swelling attending to the ENT opd at our hospital. Pearson chi square test used as statistical tool to analyse the data. All patients informed written consent taken. The patients are subjected to detailed history with thorough clinical examination, pathological and radiological investigation. FNAC, USG and TFT were done in each case. The result of FNAC was interpreted. Results: The present study includes 120 cases. All patient examined clinically, pathologically and radiological. The common age group of presentation of thyroid swelling is between second to fourth decade. Youngest patient is of 15 yrs. old and oldest is being 68 yrs of age. All 120 cases were evaluated preoperatively and provisional diagnosis was made on the basis of FNAC, TFT and USG. 111 Cases were operated out of total 120 cases. So, the overall accuracy of FNAC in comparisons to HPR is 99.15% with no false positive reports. Conclusions: The overall incidence of the malignancy in thyroid swelling varies from 10% to 30% according to various studies, in our study the overall incidence of malignancy in thyroid swelling was 5.8%. High index of suspicion should be kept in mind during physical examination for detection of malignancy. FNAC should be done in all cases preoperatively FNAC is safe procedure and cost effective.